Allergies about foods and drugs (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2023)
This paper summarizes food allergy, its clinic and diagnosis, and discusses the problems caused by cross-reactivity between proteins in different foods. Likewise, the prevention and treatment of food allergy and future therapeutic novelties are studied. And the most common questions from patients and their possible answers. Next, the current knowledge about adverse drug reactions, which are very important in the practice of medicine and responsible for a great morbidity-mortality and health costs, is synthesized. This chapter reviews the latest developments in understanding how drugs sensitize the infant immune system, the factors that influence the immunogenicity of drugs, and the specific responses produced by each group. The mechanisms between idiosyncratic reactions and pseudoallergic reactions are distinguished. An approach to the diagnosis of drug allergy and a summary of the essential management are made. The problem of drug addiction is also important in children and allergy to cannabis and other drugs is possible.
Keywords: Abusive drug allergies; drug allergies; food allergies.